Lattice-based cryptanalysis of RSA-type cryptosystems: a bibliometric analysis - Mengce Zheng; Hao Kang (Cybersecurity)
Abstract The RSA (Rivest–Shamir–Adleman) cryptosystem is a widely used public-key cryptographic algorithm in information systems and computer applications. With the advancement of lattice theory, a technique known as the lattice-based method has emerged as a significant threat to RSA and its variants. This paper aims to conduct a bibliometric analysis of publications in the field of lattice-based attacks on RSA-type cryptosystems. The analysis is based on a dataset of relevant publications retrieved from Scopus and utilizes visualization tools such as CiteSpace and VOSviewer for a thorough overview. In order to understand the research developmental trajectory, we analyze the publication trends over the years, explore cooperation networks at various levels, including country/region, institution, and author, and assess the extent of collaboration, contribution, and productivity within the field. Additionally, author co-citation network and reference co-citation clustering are utilized to enable the identification of significant research achievements, cutting-edge developments, and structural framework. Furthermore, we conduct detailed analysis from a keyword perspective to identify research hotspots and emerging trends. The findings contribute to the existing body of knowledge on lattice-based cryptanalysis of RSA-type cryptosystems. Moreover, this bibliometric analysis serves as a valuable resource for identifying fruitful areas for further exploration and guides future research efforts.